Electrical model of a solar car system using SIMULINK - Md. Abdullah Al Mahmud; Md. Asifuzzaman; Samadani, Md. Adnan; Alam, B.M. Asif Khurshed (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.